Analysis of plant cell death-inducing proteins of the necrotrophic fungal pathogens Botrytis squamosa and Botrytis elliptica - Malvestiti, Michele C.; Steentjes, Maikel B. F.; Beenen, Henriek G.; Boeren, Sjef; van Kan, Jan A. L.; Shi-Kunne, Xiaoqian (Frontiers in Plant Science, 2022)
Fungal plant pathogens secrete proteins that manipulate the host in order to facilitate colonization. Necrotrophs have evolved specialized proteins that actively induce plant cell death by co-opting the programmed cell death machinery of the host. Besides the broad host range pathogen Botrytis cinerea, most other species within the genus Botrytis are restricted to a single host species or a group of closely related hosts. Here, we focused on Botrytis squamosa and B. elliptica, host specific pathogens of onion (Allium cepa) and lily (Lilium spp.), respectively. Despite their occurrence on different hosts, the two fungal species are each other’s closest relatives. Therefore, we hypothesize that they share a considerable number of proteins to induce cell death on their respective hosts. In this study, we sequenced and assembled high quality genomes, which enabled us to perform synteny analysis. To assess the cell death-inducing capacity of their secreted proteins, we produced culture filtrates of B. squamosa and B. elliptica that induced cell death responses upon infiltration in host leaves. Protein composition of the culture filtrate was analysed by mass spectrometry, and we identified orthologous proteins that were present in both samples. Subsequently, the expression of the corresponding genes during host infection was compared. The analysis of cell death-inducing proteins of B. squamosa and B. elliptica provides insights in the mechanisms used by these two Botrytis species to infect their respective hosts.